2017
DOI: 10.1596/1813-9450-8161
|View full text |Cite
|
Sign up to set email alerts
|

Does Financial Education Impact Financial Literacy and Financial Behavior, and If So, When?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 24 publications
3
89
0
2
Order By: Relevance
“…Many of these studies are based on randomized control trails, studying poor people in developing countries. Results of these studies show that the effect of financial literacy training is small (Fernandes et al, 2014), but training is more effective in improving savings behaviors than borrowing behaviors (Kaiser and Menkhoff, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies are based on randomized control trails, studying poor people in developing countries. Results of these studies show that the effect of financial literacy training is small (Fernandes et al, 2014), but training is more effective in improving savings behaviors than borrowing behaviors (Kaiser and Menkhoff, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The significance of the current findings is that they prove, through the example of Hungary, that financial awareness closely correlates with household saving and borrowing patterns (for its international background, see Mitchell Nevertheless, financial literacy can only be significantly shaped over the long term, if at all. Given on 126 impact analyses, Kaiser and Menkhoff concluded that financial training courses improve the population's financial skills in general, but typically not in the case of lower-income social layers (Kaiser & Menkhoff, 2017). On the other hand, borrowing habits are extremely difficult to influence, irrespectively of social layers.…”
Section: Financial Literacy In the International Literaturementioning
confidence: 99%
“…In a meta-analysis of 126 evaluation studies, financial education has been found to have a significant impact on financial behavior and, to an even greater extent, on financial literacy. The success of the intervention is fundamentally dependent on increasing the intensity of education and the provision of financial education (Kaiser, Menkhoff, 2017). The other author's study uses school reforms as intermediaries for the growth of quantitative skills but does not contain any direct quantitative skills or financial literacy.…”
Section: Cultivating Human Capital As An Education Focused On Entreprmentioning
confidence: 99%